2017
DOI: 10.1007/s00268-017-4192-3
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Prognostic Role of 18‐FDG PET/CT in the Management of Resectable Biliary Tract Cancer

Abstract: PET/CT is a reliable imaging modality for metastatic lymph node detection in cholangiocarcinoma. Tumour SUV-max is an independent factor for oncological outcomes in patients with resectable disease. For patients who have TNM stage I or II cholangiocarcinoma, tumour SUV-max over 8 is associated with significantly inferior disease-free and overall survival even after curative resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 49 publications
1
24
2
1
Order By: Relevance
“…Very few studies assessed the role of FDG-PET for the evaluation of nodal status, and no recommendations can be drawn because of conflicting results. 19 Given the high prognostic impact of positive lymph nodes in patients with large tumour burden or at increased surgical risk, preoperative endoscopic ultrasound with fine needle aspiration cytology may be considered to drive clinical decisions. Lymph node metastases beyond the hepato-duodenal and gastro-hepatic ligaments are a well-established contraindication to surgical resection.…”
Section: Clinical Diagnosis and General Principles Of Surgical Considmentioning
confidence: 99%
“…Very few studies assessed the role of FDG-PET for the evaluation of nodal status, and no recommendations can be drawn because of conflicting results. 19 Given the high prognostic impact of positive lymph nodes in patients with large tumour burden or at increased surgical risk, preoperative endoscopic ultrasound with fine needle aspiration cytology may be considered to drive clinical decisions. Lymph node metastases beyond the hepato-duodenal and gastro-hepatic ligaments are a well-established contraindication to surgical resection.…”
Section: Clinical Diagnosis and General Principles Of Surgical Considmentioning
confidence: 99%
“…13,15 Recent data have suggested that standard uptake max may have prognostic implications and cut-offs may be able to distinguish between benign and malignant strictures among those with and without PSC. 16,17 Larger cohorts comprised of PSC patients are needed to determine if these observations can be applied in this unique population. Among these modalities, MRI/MRC is the diagnostic technique of choice.…”
Section: Noninvasive Imagingmentioning
confidence: 99%
“…F-18-FDG PET/BT gastrointestinal sistem kanserlerinde evreleme, hastalık rekkürensini saptama ve lezyonların benign-malign ayrımı gibi endikasyonlarla kullanılmaktadır. Yakın zamanda yapılmış çalışmada F-18-FDG PET/BT tetkiki safra yolları kanserlerinde tedavi planını yaparken lenf nodu metastazını belirlemede güvenilir olmasının yanısıra SUV max değerinin bağımsız prognostik faktör olduğunu göstermiştir (10). Vakamız F-18-FDG PET-BT'sinde ana hepatik safra kanalından koledoka 43 milimetrelik segment boyunca uzanan, en geniş yerinde 7 milimetreye ulaşan duvar kalınlaşması alanında malignite düzeyinde artmış (SUV max=6,1) FDG tutulumu saptanması nedeni ile kolanjiokarsinom öntanısı ile tarafımıza refere edilmişti.…”
Section: Discussionunclassified